2007
DOI: 10.1186/1471-2474-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree analysis and epidemiological features of idiopathic congenital talipes equinovarus in the United Kingdom: a case-control study

Abstract: BackgroundCongenital talipes equinovarus (CTEV) is a common developmental disorder of the foot, affecting between 1 and 4.5 per 1000 live births. The aetiology is not well elucidated. While both genetic and environmental factors are implicated, no specific genes have been identified and little is known about environmental risk factors.MethodsWe conducted a case-control study of idiopathic congenital talipes equinovarus (ICTEV) in the United Kingdom. 194 cases and 60 controls were recruited. Pedigrees were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 34 publications
6
41
2
Order By: Relevance
“…The findings that majority of the children affected were first-born (57.9%) of their mother was not different from results of other studies in which the association with primiparity was described (Werler et al, 2013;Cardy et al, 2007;Kancherla et al, 2010). However, this study went a step further to show the number of males and females involved even though this was found not to be statistically significant.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The findings that majority of the children affected were first-born (57.9%) of their mother was not different from results of other studies in which the association with primiparity was described (Werler et al, 2013;Cardy et al, 2007;Kancherla et al, 2010). However, this study went a step further to show the number of males and females involved even though this was found not to be statistically significant.…”
Section: Discussioncontrasting
confidence: 52%
“…In our study majority of the mothers were of young age, although "maternal age has been shown to be both inversely and positively associated with clubfoot" (Cardy et al, 2007;Dickinson et al, 2008;Kancherla et al, 2010). Some studies differ in opinion in that they found no association (Werler et al, 2013;Pavone et al, 2012;Carey et al, 2005;Skelly et al, 2002).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…This limb deformity is known as idiopathic congenital talipes equinovarus (ICTEV) (1)(2). Neurological, muscular, bony, vascular and connective tissue mechanisms have been hypothesized to be involved in the pathology of ICTEV; however, the specific roles of these mechanisms in ICTEV remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological, muscular, bony, vascular and connective tissue mechanisms have been hypothesized to be involved in the pathology of ICTEV; however, the specific roles of these mechanisms in ICTEV remain unclear. Previous studies in twins and various ethnicities, as well as pedigree analyses, have indicated that a genetic basis in combination with additional environmental factors is responsible for ICTEV (2)(3)(4)(5)(6). It is becoming increasingly clear that genetic factors are important for the pathogenesis of ICTEV.…”
Section: Introductionmentioning
confidence: 99%